Art-Based Workshops for Women: An Opportunity for Reflection on Identity and Transformation following Cancer Treatment - Marie-Christine Ranger; Sandra Houle; Alysson Rheault; Roanne Thomas (Occupational Therapy International)
Individuals experiencing cancer often report feelings of abandonment by the healthcare system after medical treatment has ended. Specifically, women with cancer have expressed the need for support beyond traditional medical and rehabilitation periods, especially with the process of reconstructing the self in the context of enduring illness. Occupational therapists could play a critical role in providing opportunities for self-reflection and transformation through occupation for this population. Art-based occupations may be especially useful for providing space for self-reflection and personal change. This article describes the experiences of women living with cancer who participated in community art-based workshops that focused on the themes of identity and transformation. The project consisted of mixed-media workshops that were held at a community-based facility providing supportive programs for people living with cancer. Eleven women participated in the workshops led by an art-based rehabilitation researcher and a visual artist. Workshops were audio-recorded, and photographs of the participants’ artwork were taken. Individual postworkshop interviews were conducted with the participants, within 4 to 6 weeks following the last workshop. Interpretive description was used to capture four themes with implications for personal change, transformation, and occupational therapy: (1) revealing: therapeutic potential; (2) sharing: vulnerability and new perspectives; (3) transforming: the self; and (4) creating: regular practices. The findings point to ways occupational therapists can form new partnerships with other disciplines and professionals to generate positive outcomes for people living with cancer.